2014
DOI: 10.1097/inf.0000000000000250
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Birth Month on the Risk of Respiratory Syncytial Virus Hospitalization in the First Year of Life in the United States

Abstract: Birth month and age at admission impacted the risk of RSV-related hospitalization within the first year of life in 5 states we investigated. As RSV vaccine candidates are currently under investigation in clinical trials, our findings help identify ideal RSV vaccine schedules to prevent early and severe events while improving the use of expensive prophylactic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 19 publications
4
23
0
Order By: Relevance
“…Our study provides further evidence for several high-risk groups and known risk factors for RSVH, including birth in proximity to the RSV season, maternal smoking, low social class/deprivation, male sex, siblings in the household, and multiple births [19][20][21]. Children born prematurely were found to be at increased risk of RSVH, including those born moderate-late preterm (33-35 wGA), where the incidence was more than double that in term children (4.6% vs. 1.9%, respectively; p < 0.0001).…”
Section: Maximal Burden Of Rsvhmentioning
confidence: 51%
“…Our study provides further evidence for several high-risk groups and known risk factors for RSVH, including birth in proximity to the RSV season, maternal smoking, low social class/deprivation, male sex, siblings in the household, and multiple births [19][20][21]. Children born prematurely were found to be at increased risk of RSVH, including those born moderate-late preterm (33-35 wGA), where the incidence was more than double that in term children (4.6% vs. 1.9%, respectively; p < 0.0001).…”
Section: Maximal Burden Of Rsvhmentioning
confidence: 51%
“…Our findings regarding the relative burden of RSV-and influenza-attributable hospitalization across overlapping age groups are also in agreement with other modeling studies [2, 8], but ours is the only study to investigate the RSV burden both in school children and in older seniors aged 75+ years. A caveat to our data is that most RSV hospitalizations occur in children less than 1 year of age [30], but we did not stratify the <5 years age group to give more age-specific estimates. Stratification of this age group would also be useful for influenza estimates.…”
Section: Discussionmentioning
confidence: 99%
“…A study from the United Kingdom reported higher risk in children younger than one year born between September and November, coinciding with their RSV outbreak beginning slightly earlier (between weeks 41 to 43) [ 27 ]. In the USA, infants under one year born in December and January have a greater risk of being hospitalized [ 28 ]. In Spain, greater risk of being admitted due to RSV has been described in children born during the second half of the year [ 12 ].…”
Section: Discussionmentioning
confidence: 99%